Role of Financial Performance Determines the Sustainability of Operating Profit Growth - Prasetiyo, Yudhi (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2024)
During the COVID-19 pandemic that has hit the entire world, businesses are facing challenges in starting their business development due to financial factors. The movement of company profits shows business development, which is an indicator of business progress. The entity calculates and considers business conditions based on existing performance. The aim of this research is to observe and analyze how financial performance and business operational results influence the movement of company profits in various industrial companies on the Indonesia Stock Exchange from 2016 to 2021. This research uses a quantitative exploratory basis. The number of various industrial companies listed on the Indonesian Stock Exchange reached 126 companies. The purposive sampling process uses secondary data from the Indonesian Stock Exchange database. In this research, multiple regression is used to analyze. The research results show that the increase in profits is not significantly influenced by financial performance, which is measured by activity ratios, liquidity, profitability and solvency using the measurement proxies used in this research. Keywords: Ratio Activity; Ratio Liquidity; Ratio Profitability; Ratio Solvency; Profit Growth